Kantian Ethical Humanism in Late Imperial Russia - Thomas Nemeth (Кантовский сборник, 2018)
The cultural movement known as “humanism” has unfortunately not received a clear and careful definition. Historians and philosophers have lumped together their various understandings of outlooks that stress the value and importance of human life under the collective term “humanism.” This essay sets out to contrast, in particular, three types of humanism, all of which attracted attention at overlapping times in Imperial Russia and then the Soviet Union. The youngest of the three, Marxist humanism, stemmed from late Soviet-era philosophers, who advocated the idea that the human individual as such had a timeless intrinsic value. A second form of humanism, Christian humanism, emerged slowly in nineteenth-century Russia under the influence of Slavophilism. The Slavophiles with a deep sense of religiosity rooted in an understanding of the Church Fathers. They rejected the role of reason in evaluating moral choices, relying on faith to reveal objective moral laws and rules. Their form of Christian humanism lay in a commitment to justice and respect for all human beings. However, the arguably most historically significant Christian humanist in this era was Vladimir S. Solovyov, who went on to combine influences from Slavophilism and the third type of humanism, Kantian humanism. This third type of humanism professedly relied on reason alone, not metaphysical foundations. Solovyov, however, ultimately grounded his moral doctrine in a highly metaphysical all-unity, which he saw as Reason — note the capital “R” — with human civilisation historically unfolding towards a Kingdom of God on Earth. There were other notable advocates of a Kantian humanism in Imperial Russia, but one that cannot be forgotten is Boris N. Chicherin, who combined Kantian morality with a distinct favouring of Hegelianism. What emerges most strongly in the repeated attempts to construct a humanistic ethics in late Imperial Russia and into the Soviet period is that Kant’s powerful and pervasive philosophical presence could not be ignored.